Making a Decision to Study in the Field of Public Administration, Faculty of Humanities and Social Sciences, Rajabhat Thepsatri University - Teedee, Thatchapon; Pansamai, Juthamard; Sanwised, Chalida (Interdisciplinary Academic and Research Journal, 2023)
Studying in higher education institutions is an important option to create opportunities and develop oneself to their full potential. However, when choosing a higher education institution or field of study that is suitable for one’s interests and aptitudes, one should decide on the field of study in line with one’s own expectations. The concepts affecting the decision to study in educational institutions can be divided into 5 aspects including; 1) the image of the university, 2) the location, 3) the public relations, 4) the curriculum, and 5) the expectation of employment. Therefore, this research aims to 1) study the level of decision-making in the field of Public Administration, Faculty of Humanities and Social Sciences, Rajabhat Thepsatri University 2) compare the level of decision-making to study in the field of Public Administration, Faculty of Humanities and Social Sciences, Rajabhat Thepsatri classified by sex, domicile, and average parental income. The sample group was students from the Department of Public Administration, regular semester, academic year 2023, amount 92 people using Krejcie & Morgan’s sampling table at 95% confidence level. The tool used to collect data was a questionnaire. Quantitative data were analyzed using statistics including percentage, mean, standard deviation, T-Test, and F-Test, One-Way ANOVA. The results of the research revealed that (1) the overall level of decision-making study in the field of Public Administration was at a high level. Considering each aspect, it was found that the aspect of expectation and employment at the highest level and a high level in 4 aspects by following; curriculum, location, public relations, and university image. And (2) Comparing the level of decision-making to further study by sex, domicile, and average family income was not statistically significant at 0.05 level.